2010
DOI: 10.1002/jsfa.4073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium form on blood and milk selenium concentrations, milk component and milk fatty acid composition in dairy cows

Abstract: Supplementation of diet with SY appears to be of more benefit than SS in producing favorable milk with high PUFA and Se concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 26 publications
9
30
0
9
Order By: Relevance
“…Likewise, Sun et al (2017) found no effect of Se sources (hydroxyselenomethionine and sodium selenite) and Se supplementation (0.1, 0.3, or 0.5 mg of Se kg -1 DM) compared to a basal diet containing 0.06 mg of Se kg -1 DM in mid lactation cows. Additionally, milk yield and composition in the present study were supported by other (Calamari et al, 2010;Gong et al, 2014;Heard et al, 2007;Juniper, Phipps, Jones, & Bertin, 2006;Ran et al, 2010;Salman et al, 2013) reporting dietary Se source did not markedly affect milk yield or composition in lactating cows.…”
Section: Milk Production and Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, Sun et al (2017) found no effect of Se sources (hydroxyselenomethionine and sodium selenite) and Se supplementation (0.1, 0.3, or 0.5 mg of Se kg -1 DM) compared to a basal diet containing 0.06 mg of Se kg -1 DM in mid lactation cows. Additionally, milk yield and composition in the present study were supported by other (Calamari et al, 2010;Gong et al, 2014;Heard et al, 2007;Juniper, Phipps, Jones, & Bertin, 2006;Ran et al, 2010;Salman et al, 2013) reporting dietary Se source did not markedly affect milk yield or composition in lactating cows.…”
Section: Milk Production and Compositionsupporting
confidence: 88%
“…They reported a higher BW for supplemented cows with selenite compared to yeast Se which might be due to differences in BW at enrollment. In according to the present study results, other studies investigating the effects of dietary Se source in lactating cows did not observe any change in DMI (Heard et al, 2007;Ran et al, 2010;Salman et al, 2013;Sun et al, 2017).…”
Section: Dry Matter Intake Body Weight and Body Condition Score Changessupporting
confidence: 78%
“…Dietary supplementation with Se yeast in lactating dairy cows increased Se milk concentrations in Australia [147]. In China, supplementation of diet with Se-enriched yeast was more effective than sodium selenite in producing favorable cow milk with high polyunsaturated fatty acids and Se concentrations [67]. In a similar study, Holstein cows' diet was supplemented with either Se yeast or selenite.…”
Section: Food Fortification: Meat Milk and Eggsmentioning
confidence: 93%
“…Selenium supplementation in diets usually results in an increase of the selenium content and GSH-Px activity in the blood of calves [64], heifers [65] and fattening bulls [66]. Such positive effects become more pronounced when Se is supplemented in organic form as compared to inorganic form [65,67]. Generally, organic Se supplementation resulted in an estimated 20% increase Se level and 16% increase in GSH-Px activity in blood [68].…”
Section: Assessment Of Selenium Nutritional Status In Animalsmentioning
confidence: 99%
“…It is one of the last proteins to be affected in the event of Se deficiency. Selenium supplementation may reduce the incidence of metritis and ovarian cysts during the postpartum period [17,18], reported that adding Se to cows diet significantly increased Se content and percentage of polyunsaturated fatty acids (PUFA) in milk. Several studies have demonstrated the beneficial effects of supplemental selenium or iodide in maintaining thyroid gland and immune competence, and reducing ovarian cysts Mehdi, Dufrasne [19].…”
Section: /2mentioning
confidence: 99%